2017
DOI: 10.1074/jbc.m117.784165
|View full text |Cite
|
Sign up to set email alerts
|

Computational tools help improve protein stability but with a solubility tradeoff

Abstract: Accurately predicting changes in protein stability upon amino acid substitution is a much sought after goal. Destabilizing mutations are often implicated in disease, whereas stabilizing mutations are of great value for industrial and therapeutic biotechnology. Increasing protein stability is an especially challenging task, with random substitution yielding stabilizing mutations in only ∼2% of cases. To overcome this bottleneck, computational tools that aim to predict the effect of mutations have been developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
118
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 103 publications
2
118
0
Order By: Relevance
“…performed their predictions by using a sophisticated approach to gain a consensus sequence by comparing calculations with closely related enzymes to increase the stability . Using this strategy, the thermostability was increased for the fungal cellobiohydrolase I by 2.1 °C by single mutation, and the authors showed that 24 % of their selected FoldX predictions were stabilizing . We also found that approximately 20 % of the predicted mutant proteins that we expressed resulted in stabilization.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…performed their predictions by using a sophisticated approach to gain a consensus sequence by comparing calculations with closely related enzymes to increase the stability . Using this strategy, the thermostability was increased for the fungal cellobiohydrolase I by 2.1 °C by single mutation, and the authors showed that 24 % of their selected FoldX predictions were stabilizing . We also found that approximately 20 % of the predicted mutant proteins that we expressed resulted in stabilization.…”
Section: Resultsmentioning
confidence: 74%
“…We also found that approximately 20 % of the predicted mutant proteins that we expressed resulted in stabilization. In contrast, by using only random‐based approaches, the success rate tends to be approximately 2 % …”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The thermal stability meta‐predictor tool was used to predict the effect of missense ZnT2 mutations on the thermal stability of the protein. This tool combines the predictive power of 11 tools to generate two predictive scores, an average from all the tools, as well as a weighted average which takes into consideration the amino acid environment . The weighted average is considered more accurate .…”
Section: Methodsmentioning
confidence: 99%
“…Alterations to the protein core from complete protein redesign may result in low thermodynamic stability and periodic fluctuations that expose the interior of the protein to solvent, creating a surface favorable for aggregation. Explicit consideration of solubility in design, either with a scoring term that disfavors hydrophobic patches on the surface [189], or solubility prediction based on sequence threading [190,191], may be effective in increasing protein yield and in vivo efficacy.…”
Section: Challenges In Automated Protein Designmentioning
confidence: 99%